What is the Best Strategy to Develop Creative Industry in Indonesia? - Muhammad Adhi Prasnowo; Gusti Adriansyah; Khoirul Hidayat (Universitas Sebelas Maret, 2018)
Small and Medium Enterprises (SMEs) have an important role and strategic for economic growth. This is because at the time of the economic crisis in Indonesia, SMEs are the economic sectors which have the most excellent durability. Wedoro Village in Sidoarjo city, Indonesia, is famous for the footwear creative industry especially slippers and shoes. A wide variety of slippers and shoes with different types available. Stores and outlets are widespread across the village. Wedoro region has been known as one of the predecessors of creative industries in the field of footwear. Currently the industrial centres of creative footwear is experiencing a decline in sales compared with its heyday in 2001-2006 years ago. This research aims to design a development strategy of the creative industry centre in Wedoro by using SWOT analysis and grand strategy. The results of this study indicate that the cause of the decline in sales is a flood of Chinese products, rising raw material prices, and the lack of innovation in product design. Hence, creative industry in Indonesia especially in Wedoro Village might need a guidance from the government in developing innovation in product design and marketing. It is therefore expected that the existence of a creative industry in Wedoro can grow and create occupations especially for local residents and also increase the revenue of the Sidoarjo city.